Effect of intercritical processing temperature on mechanical properties, microstructure and microhardness of ferrite - bainite medium carbon dual phase steels. Issue 1 (1st January 2021) - B M, Gurumurthy; Kini U, Achutha; Sharma, Sathyashankara; Hiremath, Pavan; M C, Gowrishankar
Abstract: This research focusses on the dual phase (ferrite and bainite) treatment for medium carbon steels containing same carbon content (different alloying elements) and mechanical properties, as well as microhardness and microstructure. Dual phase treatment is carried out by heating normalized specimen to intercritical temperature range (750, 770 and 790 °C), followed by isothermal holding in the bainitic temperature (350 °C) and cooling to room temperature in still air. The effect of chemical composition (alloying elements) of steel on the dual phase morphology intern on the mechanical properties like, tensile strength, elongation, hardness and impact energy is also presented. Mechanical property results are in par with the microstructure and microhardnss of dual phase obtained. Lower intercritical temperature (750 °C) has resulted in lesser amount of bainite phase with poor mechanical properties in dual phase structure, whereas higher temperature (790 °C) increases bainite phase content with considerable improvement in mechanical properties. Microhardness data obtained supports the qualitative analysis of microstructure in all steels under consideration. It is found that intercritical temperature of dual phase treatment and material alloying elements are the major contributing factors on the dual phase microstructure and mechanical properties.